Breastfeeding advice for reality: Women's perspectives on primary care support in South Africa. Issue 1 (12th August 2019) - Doherty, Tanya; Horwood, Christiane; Haskins, Lyn; Magasana, Vuyolwethu; Goga, Ameena; Feucht, Ute; Sanders, David; Tylleskar, Thorkild; Kauchali, Shuaib; Dhansay, Muhammad Ali; Rollins, Nigel; Kroon, Max; et al.
Abstract: Breastfeeding education and support are critical health worker skills. Confusion surrounding infant feeding advice linked to the HIV epidemic has reduced the confidence of health workers to support breastfeeding. High antiretroviral therapy coverage of breastfeeding women living with HIV, and an Infant Feeding policy supportive of breastfeeding, now provides an opportunity to improve breastfeeding practices. Challenges remain in restoring health worker confidence to support breastfeeding. This qualitative study presents findings from focus group discussions with mothers of young infants, exploring their experiences of health worker breastfeeding counselling and support. Analysis followed the thematic framework approach. Six researchers reviewed the transcripts, coded them independently, then jointly reviewed the codes, and agreed on a working analytical framework. Although mothers received antenatal breastfeeding messages, these appeared to focus rigidly on the importance of exclusivity. Mothers described receiving some practical support with initiation of breastfeeding after delivery, but support and advice for post‐natal breastfeeding challenges were often incorrect or absent. The support also ignored the context in which women make infant feeding decisions, including returning to work and pressures from family members. Despite improved breastfeeding policies, restoring confidence in health workers to support breastfeeding remains a challenge. The post‐natal period, when mothers experience breastfeeding difficulties, is particularly critical, and our findings reinforce the importance of continuity of care between communities and health facilities. This research has implications for how health workers are trained to support breastfeeding. Greater attention is needed on developing skills and confidence in identifying, assessing, and supporting women experiencing breastfeeding challenges.